Effects of Working Memory Span on Processing of Lexical Associations and Congruence in Spoken Discourse - Boudewyn, Megan A.; Long, Debra L.; Swaab, Tamara Y. (Frontiers in Psychology, 2013)
The goal of this study was to determine whether variability in working memory (WM) capacity and cognitive control affects the processing of global discourse congruence and local associations among words when participants listened to short discourse passages. The final, critical word of each passage was either associated or unassociated with a preceding prime word (e.g., “He was not prepared for the fame and fortune/praise”). These critical words were also either congruent or incongruent with respect to the preceding discourse context [e.g., a context in which a prestigious prize was won (congruent) or in which the protagonist had been arrested (incongruent)]. We used multiple regression to assess the unique contribution of suppression ability (our measure of cognitive control) and WM capacity on the amplitude of individual N400 effects of congruence and association. Our measure of suppression ability did not predict the size of the N400 effects of association or congruence. However, as expected, the results showed that high WM capacity individuals were less sensitive to the presence of lexical associations (showed smaller N400 association effects). Furthermore, differences in WM capacity were related to differences in the topographic distribution of the N400 effects of discourse congruence. The topographic differences in the global congruence effects indicate differences in the underlying neural generators of the N400 effects, as a function of WM. This suggests additional, or at a minimum, distinct, processing on the part of higher capacity individuals when tasked with integrating incoming words into the developing discourse representation.